Development effectiveness through gender mainstreaming: gender equality and povery reduction in South Asia - Kelkar, Govind (2005)
Gender mainstreaming is a process to achieve greater gender equality and overcome the costs of women's marginalisation. Unequal gender relations distribute the burden of poverty disproportionately on women. They can also be the cause of poverty among women and girls in non-poor families. These unequal relations therefore need to be addressed both as a cause and as a factor in the intensification of poverty. Empowerment of women has to go beyond mere instrumentalism and begin with first addressing questions of women's agency, their well-being and self-esteem and then that of their families and communities. - Reproduced.
Keywords: Poverty - South Asia; Women and development - South Asia; Women and development